Optimizing the Organization of Statistical Activities through the Revision of Law No. 16 of 1997 Concerning Statistics - Yuliarto, Ramdhanul; Zeinudin, Moh.; Warka, Made (Journal of Progressive Law and Legal Studies, 2023)
This research to find out and study how implementation of basic statistics carried out by the Central Statistics Agency based on Law Number 16 of 1997 concerning Statistics (Statistics Law); what are the obstacles in optimizing the implementation of basic statistics and how to overcome the obstacles in implementing basic statistics optimally through reform of the Statistics Law. This research is normative legal research with a legal political and legal sociology approach, which examines the Statistics Law as positive law in the administration of basic statistics and formulates legal substance that should be implemented in the future. The data source is secondary data consisting of primary legal materials and secondary legal materials. Data collection methods use library studies and interviews. Primary legal materials and secondary legal materials are analyzed using legal analysis methods. The deductive thinking process is used to draw conclusions. The theoretical basis used as an analytical tool in reviewing research results and discussions is the theory of legal effectiveness and public policy theory. The results of this research indicate that the implementation of basic statistical activities by BPS based on the Statistics Law is not running optimally because there are obstacles, such as: low public awareness of the importance and usefulness of statistics, the application of criminal sanctions for respondents that are not effective and statistical data in ministries/ Partial government institutions. These obstacles are fundamental and cannot be overcome casuistically but must be done with comprehensive and revolutionary efforts, so efforts to overcome them are by reforming the Statistics Law so that the implementation of basic statistical activities by BPS can run optimally. From this explanation it can be concluded that in order to obtain legal certainty for both BPS officers and respondents, an article is needed that guarantees legal certainty so that if respondents refuse, they can be given sanctions which of course must be regulated in the Law on Statistics. We as authors propose and suggest that the Government can immediately update the Statistics Law and correct the weaknesses we have mentioned above.